Lessons learned from 25 years of operational large-scale restoration: The Sow-A-Seed project, Sabah, Borneo - E. Petter Axelsson; Kevin C. Grady; David Alloysius; Jan Falck; Daniel Lussetti; Charles Santhanaraju Vairappan; Yap Sau Wai; Keiko Ioki; Maria Lourdes T. Lardizabal; Berhaman Ahmad; Ulrik Ilstedt (Ecological Engineering, 2024)

Moderate thermal post-treatment of digestate to improve biomethane production from agricultural- and food waste - Mette Axelsson Bjerg; Eva-Maria Ekstrand; Ingrid Sundgren; Sepehr Shakeri Yekta; Jan Moestedt; Annika Björn (Bioresource Technology Reports, 2024)

Geothermal-solar integrated Multistage Flash Distillation Cogeneration system: A cleaner and sustainable solution - Kriti Yadav; Maria Gudjonsdottir; Guðni Axelsson; Málfríður Ómarsdóttir; Anirbid Sircar; Manan Shah; Apurwa Yadav (Desalination, 2023)

Evaluating caprine remains of the Swedish Funnel Beaker culture through ZooMS - Karl-Göran Sjögren; Michael Buckley; Maria Vretemark; Tony Axelsson (Archaeological and Anthropological Sciences, 2023)
In northern Europe, the first indications of a Neolithic lifestyle appear around 4000 cal BC from northern Germany up to middle Sweden and south-eastern Norway in an apparently short period of time, largely carried by immigrant populations bringing new species of plants and animals into the region. However, the nature of this domestication “package” is not everywhere the same, whereby both environmental and cultural filters acted on the particular set of species cultivated and bred in different regions. In Neolithic Scandinavia, cattle, pigs, and caprines (sheep and goat) are all present in varying proportions, with cattle more prominent in Denmark and pigs more prominent in more northerly areas. However, little is known about the ratio of sheep to goat remains within this region, largely due to difficulties in morphologically separating the two species. In this paper, we report the results from ZooMS analysis of 45 sheep/goat bone samples from two recently excavated Funnel Beaker settlements in Karleby, Falbygden, Sweden. The ZooMS analyses gave a clear and somewhat surprising result: 33 of the samples were classed as sheep, one as deer, and none of them as goat. In all likelihood, goats have not been present at all on these sites. A survey of the literature shows that while small numbers of goats are likely present in Denmark from the Early Neolithic, their presence in Sweden at this time is ambiguous and the few claims merit reassessment. Furthermore, the low numbers in Scandinavia compared to central and southern Europe suggests an overall geographic trend, with decreasing proportions of caprines as well as goats in the north.

Contagiousness in treated HIV-1 infection - Jaran Eriksen; Jan Albert; Maria Axelsson; Torsten Berglund; Johanna Brännström; Hans Gaines; Magnus Gisslén; Peter Gröön; Per Hagstam; Lars Navér; Karin Pettersson; Jenny Stenkvist; et al. (Infectious Diseases, 2021)

On the road to ‘research municipalities’: analysing transdisciplinarity in municipal ecosystem services and adaptation planning - Ebba Brink; Christine Wamsler; Maria Adolfsson; Monica Axelsson; Thomas Beery; Helena Björn; Torleif Bramryd; Nils Ekelund; Therese Jephson; Widar Narvelo; Barry Ness; K. Ingemar Jönsson; et al. (Sustainability Science, 2018)

Six-week follow-up after HIV-1 exposure: a position statement from the Public Health Agency of Sweden and the Swedish Reference Group for Antiviral Therapy - Hans Gaines; Jan Albert; Maria Axelsson; Torsten Berglund; Magnus Gisslén; Anders Sönnerborg; Anders Blaxhult; Gordana Bogdanovic; Maria Brytting; Christina Carlander; Leo Flamholc; Per Follin; et al. (Infectious Diseases, 2016)

Discrimination of Nuclear Explosions against Civilian Sources Based on Atmospheric Xenon Isotopic Activity Ratios - Martin B. Kalinowski; Anders Axelsson; Marc Bean; Xavier Blanchard; Theodore W. Bowyer; Guy Brachet; Simon Hebel; Justin I. McIntyre; Jana Peters; Christoph Pistner; Maria Raith; Anders Ringbom; et al. (Pure and Applied Geophysics, 2010)